2003
DOI: 10.1055/s-2003-44817
|View full text |Cite
|
Sign up to set email alerts
|

Mepivacaine for Spinal Anesthesia in Parturients Undergoing Elective Cesarean Delivery: Maternal and Neonatal Plasma Concentrations and Neonatal Outcome

Abstract: Particularly with short duration of surgery (21 +/- 5 min) intrathecal mepivacaine combined with fentanyl offers a favorable clinical alternative in parturients undergoing elective Cesarean delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…12 Recent data on modern formulations of mepivacaine have since demonstrated that TNS incidence is consistent with bupivacaine and other intrathecal local anesthetics. 13 Several studies have investigated mepivacaine for a variety of surgeries, including axillary brachial plexus block in the minor orthopedic forearm, wrist or hand surgery, 14 spinal anesthesia after elective Cesarean delivery, 15 knee arthroscopy surgery, 16 and lateral popliteal nerve blockade in foot and ankle surgery. 17 There was no systematic review comparing the anesthetic effects of mepivacaine with bupivacaine in adult surgical patients.…”
mentioning
confidence: 99%
“…12 Recent data on modern formulations of mepivacaine have since demonstrated that TNS incidence is consistent with bupivacaine and other intrathecal local anesthetics. 13 Several studies have investigated mepivacaine for a variety of surgeries, including axillary brachial plexus block in the minor orthopedic forearm, wrist or hand surgery, 14 spinal anesthesia after elective Cesarean delivery, 15 knee arthroscopy surgery, 16 and lateral popliteal nerve blockade in foot and ankle surgery. 17 There was no systematic review comparing the anesthetic effects of mepivacaine with bupivacaine in adult surgical patients.…”
mentioning
confidence: 99%